An Overview of the Medicinally Important Plant Type III PKS Derived Polyketides - Bisht, Renu; Bhattacharyya, Aniket; Shrivastava, Ankita; Saxena, Priti (Frontiers in Plant Science, 2021)
Plants produce interesting secondary metabolites that are a valuable source of both medicines for human use, along with significant advantages for the manufacturer species. The active compounds which lead to these instrumental effects are generally secondary metabolites produced during various plant growth phases, which provide the host survival advantages while affecting human health inadvertently. Different chemical classes of secondary metabolites are biosynthesized by plant type III polyketide synthases (PKSs). They are simple homodimeric proteins with the unique mechanistic potential to produce a broad array of secondary metabolites with simpler starter and extender units. Majorly these PKS derived products are the precursors of some important secondary metabolite pathways leading to products like flavonoids, stilbenes, benzalacetones, chromones, acridones, xanthones, cannabinoids, aliphatic waxes, alkaloids, anthrones, and pyrones. These secondary metabolites have various pharmaceutical, medicinal and industrial applications which make the biosynthesizing type III PKSs an important tool for bioengineering purposes. Because of their structural simplicity and ease of manipulation, these enzymes have garnered interest in recent years due to their application in the generation of unnatural natural polyketides and modified products in the search for newer drugs for a variety of health problems. The following review covers the biosynthesis of a variety of type III PKS-derived secondary metabolites, their biological relevance, the associated enzyme, and recent research.